Денежное обращение округи византийского Херсона в VII в. - Алексеенко, Н.А. (Материалы по археологии, истории и этнографии Таврии, 2005)
Настоящая работа предполагает публикацию двух ранее известных в литературе комплексов, но, к сожалению, не изданных, относящихся к интересующему нас времени. Первый из них - клад из района Казачьей бухты, второй - комплекс монет усадьбы надела 222 Обе находки происходят с сельскохозяйственной хоры Херсона, что позволяет на их основе сделать определенные выводы о характере и особенностях денежного обращения не самого города, а его округи. Two complexes of coins are published in this article. The hidden treasure from Kazachiya Bukhta (Cossak’s Bay) contains 27 coins, and complex of coins from the farmstead of plot 222 - 69 Late-Roman, Bosporus and Chersonesos - Byzantium coins dating back to the 4th century BC - the 7th century AD. The research of both complexes enabled us to come to the conclusion that their composition reflects the character of coinage in neighbourhood of the Chersonos by the period of Heraclius’s reign (610 - 640). The qualitative analysis of the coins shows that coinage from different centers were in circulation on the Chersonesos market during six preceding centuries.